2015
DOI: 10.1021/cs5017062
|View full text |Cite
|
Sign up to set email alerts
|

Selective Propylene Oxidation to Acrolein by Gold Dispersed on MgCuCr2O4 Spinel

Abstract: Gold nanoparticles supported on a MgCuCr2O4 spinel catalyze the aerobic oxidation of propylene to acrolein. At 200 °C, the selectivity is 83% at a propylene conversion of 1.6%. At temperatures above 220 °C, propylene combustion dominates. The good performance of Au/MgCuCr2O4 in selective propylene oxidation is due to the synergy between metallic Au and surface Cu+ sites. Kinetic experiments (H2 addition, N2O replacing O2) show that the reaction involves molecular oxygen. DFT calculations help to identify the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 45 publications
(85 reference statements)
1
17
0
1
Order By: Relevance
“…In addition, recent theoretical studies by Song et al . 45 46 also proposed a relevant mechanism for CO oxidation and propylene oxidation at an isolated Au site, which are compatible with our findings.…”
Section: Resultssupporting
confidence: 90%
“…In addition, recent theoretical studies by Song et al . 45 46 also proposed a relevant mechanism for CO oxidation and propylene oxidation at an isolated Au site, which are compatible with our findings.…”
Section: Resultssupporting
confidence: 90%
“…Anyway, the simple oxide Cu 2 O is reported to exhibit significant activity and selectivity and has been often chosen as a model catalyst for the determination of the involved reaction mechanism [4]. It was reported that catalytic activity of Cu 2 O catalyst system is lower than that of bismuth molybdate catalysts; therefore, the Cu 2 O catalyst is less popular [56].…”
Section: Catalystsmentioning
confidence: 99%
“…However, plenty of acrylic acidrich wastewater was generated by this procedure. [1][2][3] There are two kinds of approaches for this kind of wastewater including incineration and recycling. Recycling the wastewater is better than burning it.…”
Section: Introductionmentioning
confidence: 99%
“…Now, about 80% of acrolein has been produced by the oxidation of propylene. However, plenty of acrylic acid‐rich wastewater was generated by this procedure . There are two kinds of approaches for this kind of wastewater including incineration and recycling.…”
Section: Introductionmentioning
confidence: 99%